Synthesis and characterization of polymeric nanoparticles based on albumin - Kreuter, J.; Burkeyev, M.Zh.; Tazhbayev, Ye.M.; Kazhmuratova, A.T.; Zhumagalieva, T.S.; Zhaparova, L.Zh.; Borsynbayev, A.S.; Zhunusova, S.M. (Изд-во КарГУ, 2013)
The influence of different factors (pH of medium, nature and quantity of solvent, etc.) on physicochemical characteristics of polymeric albumin nanoparticles has been investigated in this article. Using optimal condi- tions which have been found out empty albumin nanoparticles with satisfactory physicochemical characteris- tics (particle diameter in the range of 50–100 nm, polydispersity 0.130–0.180 and ζ-potential –11,3–31,0 mV) have been obtained. Synthesized nanoparticles are promising as drug delivery systems.
Keywords: albumin; nanoparticles; glutaraldehyde; desolvating agent; immobilization; desolvation; polydipersity; particle size